(untitled) (Publicaciones en Ciencias y Tecnología, 2017)
This work specifies Autonomous Cycles (AC) of data analysis tasks, to optimize the Quality Of Services (QoS) on the Internet. The mechanisms to improve QoS on the Internet are important for Internet Service Providers (ISP). These mechanisms should be based on context analysis, Deep Packet Inspection (DPI), the use of data mining and semantics, among others. The ACs of data analysis proposed in this work integrate these aspects, to perform tasks to improve QoS on the Internet, such as the task of classifying traffic on the network. In this paper the MIDANO methodology is used, to specify the two ACs that are proposed, one with the aim of improving the QoS on the Internet, and another with the objective of learning the traffic pattern in the network. In addition, this work implements the AC that improves the QoS on the internet. This AC monitors the state of Internet traffic, determines the behavior of applications, characterizes traffic patterns, generates traffic optimization rules, among other things, using DPI techniques, semantic mining, machine learning, among others.